Implementasi Pendidikan Islam dalam Ajaran Tarjumah Jam’iyah Rifa’iyah di Dusun Luwihan, Kecamatan Kalikajar, Kabupaten Wonosobo - Alif Laifudin; Robingun Suyud El Syam; Ali Imron (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to describe the implementation of Islamic education in the teachings of Tarjumah Jam'iyah Rifa'iyah in Luwihan Hamlet, Kalikajar District, Wonosobo Regency. Qualitative setting field research takes the object of the implementation of Islamic education in the teachings of Tarjumah Jam'iyah Rifa'iyah, located in Luwihan Hamlet, Kalikajar District, Wonosobo Regency for two months from March to April 2025, with research subjects including the congregation of the sect, community leaders, and religious leaders. Data were obtained through interviews, observations, and documentation to then be analyzed descriptively. The results of the research show that the Tarjumah teachings are a legacy of K.H. Ahmad Rifa'i's thoughts which emphasize three main principles in Islamic education, namely the formation of strong faith, the development of noble morals (akhlaqul karimah), and the practice of Islamic law as a whole (kaffah). This concept not only emphasizes theoretical or cognitive aspects, but also focuses on the formation of real character and behavior in accordance with Islamic values ​​in everyday life. The implementation of Islamic education in this teaching is carried out through various religious activities that are integrated with community life, such as regular religious studies in mosques, prayer rooms, or residents' homes, with the main material in the form of Javanese tarjumah books containing Islamic teachings in the form of nadham, including aqidah, worship, muamalah, and manners. In addition, the implementation of congregational worship such as the five daily prayers, dhuha prayers, and dhikr activities, are also effective educational media. This fact shows the harmony between teaching, habituation, and exemplary behavior, where Islamic values ​​are not only taught, but are manifested in social interactions in society through joint religious activities, traditions of mutual assistance, concern for the environment, and efforts to maintain social harmony. Thus, Islamic education in the teachings of Tarjumah Jam’iyah Rifa’iyah has proven to be able to form a society that is religious, has character, and consistently practices Islamic teachings in everyday life. This finding leads to the direction of future research to examine more widely the comparative implementation of tarjumah teachings in other regions and its impact on positive social change in more depth.